Valganciclovir as Add-on to Second-Line Therapy in Patients with Recurrent Glioblastoma - Pantalone Mattia Russel; Rahbar Afsar; Söderberg-Naucler Cecilia; Stragliotto Giuseppe (MDPI, 2022)
Simple Summary
Patients with glioblastoma have a dismal prognosis. The major challenge with this disease is that it recurs despite aggressive first-line therapy and rapidly becomes therapy resistant. Cytomegalovirus has been found in most glioblastoma tumors and may contribute to tumor aggressiveness. Antiviral therapy may thus represent a novel therapeutic strategy and has shown promising results in patients with newly diagnosed glioblastoma. We performed a retrospective analysis of survival data of 29 patients with recurrent glioblastoma receiving the antiviral drug valganciclovir as an add-on to second-line therapy and of 109 contemporary controls treated at our institution. Valganciclovir was well tolerated and seemed to improve survival after tumor recurrence in patients with recurrent disease both in re-operated and non-re-operated patients and in patients with unmethylated and methylated MGMT promoter status. Prospective controlled clinical studies on patients with recurrent glioblastoma are warranted to evaluate if valganciclovir treatment offers a novel therapeutic option.
Glioblastoma invariably recurs despite aggressive and multimodal first-line treatment and no standardized second-line therapy exists. We previously reported that treatment with the antiviral drug valganciclovir as an add-on to standard therapy significantly prolonged overall survival in 102 patients with newly diagnosed glioblastoma compared to contemporary controls. Here we present the results of retrospective survival analyses including patients with glioblastoma that initiated valganciclovir therapy after recurrence. Twenty-nine patients with recurrent glioblastoma received valganciclovir as an add-on to second-line therapy at Karolinska University Hospital. Contemporary controls were 109 patients with glioblastoma who received similar second-line therapy at our institution. We retrospectively analyzed survival data of these patients. Patients with recurrent glioblastoma who received valganciclovir had longer median overall survival after recurrence than controls (12.1 vs. 7.4 months, respectively, p = 0.0028). The drug was well tolerated. Both patients who underwent re-operation and patients that were not re-operated after recurrence benefitted significantly from valganciclovir therapy. Valganciclovir prolonged survival after recurrence both in patients with an unmethylated and methylated MGMT promoter gene. Valganciclovir was safe to use and prolonged median survival after recurrence for patients with recurrent glioblastoma, re-operated or not after recurrence, and with methylated or unmethylated MGMT promoter gene.